Detection of Mycobacterium bovis in nasal swabs from communal goats (Capra hircus) in rural KwaZulu-Natal, South Africa - Cooke, Deborah M.; Clarke, Charlene; Kerr, Tanya J.; Warren, Robin M.; Witte, Carmel; Miller, Michele A.; Goosen, Wynand J. (Frontiers in Microbiology, 2024)
Animal tuberculosis, caused by Mycobacterium bovis, presents a significant threat to both livestock industries and public health. M. bovis tests rely on detecting antigen specific immune responses, which can be influenced by exposure to non-tuberculous mycobacteria, test technique, and duration and severity of infection. Despite advancements in direct M. bovis detection, mycobacterial culture remains the primary diagnostic standard. Recent efforts have explored culture-independent PCR-based methods for identifying mycobacterial DNA in respiratory samples. This study aimed to detect M. bovis in nasal swabs from goats (Capra hircus) cohabiting with M. bovis-infected cattle in KwaZulu-Natal, South Africa. Nasal swabs were collected from 137 communal goats exposed to M. bovis-positive cattle and 20 goats from a commercial dairy herd without M. bovis history. Swabs were divided into three aliquots for analysis. The first underwent GeneXpert ® MTB/RIF Ultra assay (Ultra) screening. DNA from the second underwent mycobacterial genus-specific PCR and Sanger sequencing, while the third underwent mycobacterial culture followed by PCR and sequencing. Deep sequencing identified M. bovis DNA in selected Ultra-positive swabs, confirmed by region-of-difference (RD) PCR. Despite no other evidence of M. bovis infection, viable M. bovis was cultured from three communal goat swabs, confirmed by PCR and sequencing. Deep sequencing of DNA directly from swabs identified M. bovis in the same culture-positive swabs and eight additional communal goats. No M. bovis was found in commercial dairy goats, but various NTM species were detected. This highlights the risk of M. bovis exposure or infection in goats sharing pastures with infected cattle. Rapid Ultra screening shows promise for selecting goats for further M. bovis testing. These techniques may enhance M. bovis detection in paucibacillary samples and serve as valuable research tools.